Deep - Scott, Kylie (St. Martin's Griffin, 2015)
Print book : Fiction : English : First editionView all editions and formats Summary: "Their one night stand wasn't supposed to end this way ... Positive. With two little lines on a pregnancy test, everything in Lizzy Rollins' ordinary life is about to change forever. And all because of one big mistake in Vegas with Ben Nicholson, the devastatingly sexy bass player for Stage Dive. So what if Ben's the only man who's ever made her feel out of control with desire? Lizzy knows the gorgeous rock star